Workplace incivility and the professional quality of life in nurses - Nazari, Shima (Nursing ethics, 2024)
BackgroundWorkplace Incivility is a common issue in the nursing profession. Nurses who are affected by such behaviors may experience distress.ObjectivesThis study aimed to assess the relationship between workplace incivility and nurses’ professional quality of life.Research designThis cross-sectional correlational study was conducted in 2021 in “Tehran”. Data were collected using a demographic questionnaire, the Nursing Incivility Scale (NIS), and the Professional Quality Of Life scale (ProQOL). Data analysis was performed through the Pearson correlation and multiple linear regression, using the SPSS v.16.Participants and research contextParticipants were 200 nurses randomly recruited from selected hospitals of “TUMS”.Ethical considerationsThe study obtained research ethics approval and all participants were informed of the voluntary and anonymous nature of their participation.FindingsThe mean age of participants was 32.30 ± 7.22, and 76.5% were female. There was a significant correlation between the professional quality of life and workplace incivility (r = −0.23, p = .001). Multiple regression analysis between the subscales of workplace incivility and professional quality of life demonstrated that the incivility from the supervisor (β = −0.29, p = .001) and incivility from patients (β = −0.27, p < .001) can predict the compassion satisfaction dimension. The incivility from the supervisor (β = 0.24, p = .001) and incivility from patients (β = 0.26, p < .001) can explain burnout. The incivility of the patients can explain secondary traumatic stress (β = 0.14, p = .02).ConclusionThis study showed that workplace incivility is significantly related to professional quality of life. Therefore, the reduction of behaviors of incivility can lead to the improvement of the professional quality of life.